Moral Theology on Earth: Learning from Two Thomases - Cessario, Romanus (Studies in Christian ethics, 2006)
The essay considers the influence of Christian ethics within the political order. It considers first the witness of Thomas More, then developments in Roman Catholic moral theology since the Second Vatican Council, and finally the dispute over the moral evaluation of the use by AIDS-infected spouses of condoms in order to sterilise their procreative acts. The whole discussion proceeds as a commentary on what Thomas Aquinas says about the temporal promulgation of Eternal Law, and also aims to locate moral argument within the macroscopic context of divine revelation on health and salvation, which the Church must proclaim in its fullness.